Islamization of the Term “清真” (Qing Zhen): Its Analysis for Purity and Authenticity for Muslim in China - Wang, Yongbao (Journal of Al-Tamaddun, 2024)
This paper aims at examining the meaning of the two Chinese characters “清” (Qing) and “真” (Zhen” once used singly as well as combined together in the Chinese classical literatures in order to show why and how the Chinese Muslim scholars have applied and Islamized them for interpreting Islam by the Confucian ways and Taoist methods at the civilization and culture dialogue level. Further, the paper also demonstrates the evolution of “Qing Zhen” which has eventually become a special term for Muslims in China and how its connotations have currently been limited and restricted. Meanwhile, the paper discusses the related critical issues, such as the epistemology of the Ḥalāl Food and its legislation in China. Lastly, the author comes with some humble suggestions which tie with the results of the study by wishing for Muslims, in China or anywhere else, to reexamine their conducts and to reconsider how to inherit Islam as well as how to hand it down to the next generation.